Application of Fuzzy TOPSIS Method as a Decision Support System for Achievement Student Selection - Anggoro, Vani Krismo; Riski, Abduh; Kamsyakawuni, Ahmad (Jurnal ILMU DASAR, 2023)
Achievement student selection aims to appreciate students who have achieved an achievement, both in the academic and non-academic fields. This activity is carried out in stages, starting from departments, faculties, and universities, to the national level. In the selection process, several criteria were used: GPA, scientific work, presentation, English, and achievements were featured and involved several juries to avoid subjectivity in the assessment. This study aims to get the best results from the decision support system in Achievement student election in the Mathematics Department of Jember University. Therefore, we need the fuzzy TOPSIS method to avoid and minimize problems and to make multi-criteria decision-making easier. This study's ranking results were obtained from the fuzzy TOPSIS method and standardized assessment method (based on higher education guidelines). From the four candidates who participated in this selection, the two methods give different results in the last two ranks. The fuzzy TOPSIS method ranking shows the results sequentially for candidates B, C, A, and D. In contrast, and the standardized assessment method ranking shows the results sequentially for candidates B, C, D, and A. This difference is caused by the value of the criteria factor and the weight of the candidate criteria, but the fuzzy TOPSIS method is simpler than the standardized assessment method. So that it can be recommended for the next period achievement student election at the department, faculty, or university level.